A Study on Self-Motivation and Academic Achievement Among Rural Students - Beulah, Priya; SELVAKUMAR, Dr. Y. STANLY (Journal of Advanced Research in Humanities and Social Sciences; Vol 10 No 2 (2023): Journal of Advanced Research in Humanities and Social Sciences, 2023)
The objective of this study is to investigate “A Study on Self-Motivation and Academic Achievement among Rural Students”. A survey method is used in this study. The researcher developed a self-motivation scale for this study. In this study, the investigator followed the stratified random sampling procedure to select 300 samples from various high schools and higher secondary schools in Chengalpet district. Validated instruments were applied to the sample selected for the study. Data were collected from the sample and were tabulated and used for appropriate statistical techniques. The findings, implications, suggestions and conclusions drawn from the data were recorded in this study.